Metode Layanan Project Based Learning dalam Meningkatkan Motivasi Belajar Anak di Panti Asuhan - Setiyowati, Arbin Janu; Sianda, Ahmad Thoriq Tri; Rozzana, Alfian Gita; Fitriah, Alifia Aizah; Savitri, Annisa; Putri, Amelia Wahyuning; Mufida, Atika; Milenium, Bilgis Bayuti Anugrah; Dahlia, Dewi Indah; Widad, El-tsaniyah Rihlatul (Penerbit Goodwood, 2025)
Purpose: We apply guidance using the project based learning method to increase the learning motivation of children at the Mawaddah Warohmah Malang orphanage. The aim of this service is so that orphanage children have high motivation to learn even though they have limitations so that they can improve their learning outcomes at school to achieve achievements. Methodology: The method used in this research is a quasi-experiment with a Non-Equivalent Control Group design. Data collection in this research was through scale, observations and interviews. Subjects in this research were selected using purposive sampling based on certain criteria. The instrument used is the Learning Motivation Scale. Results: The results of this research are that the PJBL service method is effectively used to increase the learning motivation of children at the Mawaddah Warohmah Orphanage. This can be seen from the post-test results, there is a significant increase in the learning motivation of orphanage children. Data analysis also shows this method is effective for increasing learning motivation. Conclusions: Based on the results of the study, the Project Based Learning service method is effectively used to increase the learning motivation of the Mawaddah Warohmah Orphanage. Limitations: This study provides a transparent assessment of its scope and potential biases. Some limitations may include the small sample size and potential respondent biases. Contribution: The PJBL service method is able to increase the learning motivation of orphanage children, so that they can have a high level of responsibility to learn independently in the orphanage. It’s increased learning motivation contributes to their learning results at school.